Analysis of targeted somatic mutations in pleomorphic carcinoma of the lung using next‐generation sequencing technique. Issue 8 (23rd June 2020) - Manabe, Saki; Kasajima, Rika; Murakami, Shuji; Miyagi, Yohei; Yokose, Tomoyuki; Kondo, Tetsuro; Saito, Haruhiro; Ito, Hiroyuki; Kaneko, Takeshi; Yamada, Kouzo
Abstract: Background: Pleomorphic carcinoma (PC) of the lung is a rare type of lung cancer with aggressive characteristics and a poor prognosis. Because it is rare, the molecular characteristics of PC remain unclear. Methods: A gene mutation analysis was performed using next‐generation sequencing (NGS) in patients with PC of the lung who had undergone surgical resection. Results: A total of nine patients were enrolled in the study. All the patients were male and eight had a history of smoking. Eight tumors contained spindle cells and three contained giant cells. Mutations considered significant were found in eight of the nine patients: in TP53 in five patients, in MET in two patients, and in ALK, ERBB2, PIK3CA, APC, NF1, and CDKN2A in one patient each. No EGFR mutation was detected in our analysis. Co‐mutations were detected in three patients: TP53 with MET and NF1, TP53 with ERBB2, and PIK3CA with CDKN2A . Conclusions: TP53 mutations were detected most frequently in PC of the lung with NGS analysis. Different co‐mutations were seen in several specimens. Key points: Significant findings of the study This study demonstrates that mutations in the TP53 gene are frequently found and co‐mutations are sometimes found in pleomorphic carcinoma of the lung using genomic profiling analysis. What this study adds Our results will help to analogize the genetic characteristics and potential target of molecular‐targeted agents of pleomorphic carcinoma of the lung.